TREN RISET TANAMAN OBAT DI INDONESIA DARI TAHUN 2011-2021: ANALISIS BIBLIOMETRIK MENGGUNAKAN VOSVIEWER - Afandi Afandi; Kurnia Ningsih; Tulus Junanto (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to determine the development of research on medicinal plant domains in Indonesia in Scopus indexed journals or proceedings from 2011-2021. Data was collected using the Publish or Perish application with search keywords related to medicinal plants in Indonesia, namely Indonesian medicinal plants and Indonesian herbal plants. The data storing in the form of Microsoft Excel 2013 and RIS. Microsoft Excel 2013 was used to analyze the development of the number of publications, the productivity of the authors, and the top most widely used articles for citations. The VOSViewer application version 1.6.17 using to analyze the relationship between research topics, trends, and the most frequently researched research topics. The results of this study show that the highest publication occurred in 2021, 177 publications (20.30%), while the lowest publication occurred in 2011 with 21 publications (2.41%). The 5 most productive researchers in publishing articles in 2011-2021 are Elya, B, who produced 14 published articles; Coal, who produced 13 published articles; Nisyawati and Silalahi, M produced 10 published articles; and Subositi, D produced 9 published articles. In this study, the topic that was most cited was Indonesia. Network visualization is divided into 4 clusters. The latest topics based on data from articles in this study, namely plants, traditional medicine, and medicinal plants, were the most published in 2017-2019. The most published topic was Indonesia, followed by topics such as medicine, analysis, and areas.